2011
DOI: 10.4028/www.scientific.net/amr.396-398.2452
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Detection of Crystal Violet in Aquatic Products

Abstract: It is very necessary to establish a kind of rapid and accurate method about detecting crystal violet for food security. In this paper, we summary the present progress in analyzing the crystal violet from three respects: sample pretreatment, detection tool, and quantitative calculation method, puts forward the direction of future development on the detection and analysis of crystal violet in aquatic products ,and gives some suggestions on it. It has certain reference value on the detection and analysis of relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The experimental data were analyzed through the BBD model in Design Expert 12.0.6. The quadratic polynomial regression model expressed by the actual value is shown in Formula (7). A positive value in this equation indicates that the influencing factor can improve the CV removal efficiency, while a negative value can reduce it.…”
Section: Optimization Of the CV Removal From Simulated Wastewater By Rsmmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data were analyzed through the BBD model in Design Expert 12.0.6. The quadratic polynomial regression model expressed by the actual value is shown in Formula (7). A positive value in this equation indicates that the influencing factor can improve the CV removal efficiency, while a negative value can reduce it.…”
Section: Optimization Of the CV Removal From Simulated Wastewater By Rsmmentioning
confidence: 99%
“…Several researchers have shown that CV can be reduced and metabolized into fat-soluble recessive CV through biotransformation after entering the human or animal body. Such recessive CV can endanger human health through the food chain, and it can seriously affect the edible safety of aquatic products due to its high toxicity, residue, carcinogenicity, and mutagenicity [7]. Therefore, many countries and areas, including Europe, the Americas, China, and Japan, have strictly prohibited the application of CV in aquaculture.…”
Section: Introductionmentioning
confidence: 99%